Nonlinear Inelastic Analysis of 2D Steel Frames : An Improvement of the Plastic Hinge Method - Nguyen, P. C.; Le-Van, B.; Thanh, S. D. T. V. (Engineering, Technology & Applied Science Research, 2020)
In this study, a new method for nonlinear analysis of 2D steel frames, by improving the conventional plastic hinge method, is presented. The beam-column element is established and formulated in detail using a fiber plastic hinge approach. Residual stresses of I-shape sections are declared at the two ends through fibers. Gradual yielding by residual stresses along the member length due to axial force is accounted for by the tangent elastic modulus concept. The P-δ effect is captured by stability functions, whereas the P-Δ effect is estimated by the geometric stiffness matrix. A nonlinear algorithm is established for solving nonlinear problems. The present study predicts the strength and behavior of 2D steel frames as efficiently and accurately as the plastic zone method did.